SNP rs1533428 at 2p16.3 as a marker for late-onset primary open-angle glaucoma - Chen, Li Jia (Molecular Vision, 2012)
PURPOSE: To investigate the associations between gene variants in cholesterol 24S-hydroxylase (CYP46A1), LIM homeobox transcription factor 1-beta (LMX1B), plexin domain containing 2 (PLXDC2), toll-like receptor 4 (TLR4), transmembrane and tetratricopeptide repeat containing 2 (TMTC2), zona pellucida glycoprotein 4 (ZP4), chromosome 2p16.3, and primary open-angle glaucoma (POAG). METHODS: We studied 462 POAG patients and 577 controls from three cohorts (Hong Kong, Shantou, and Beijing, China). Twelve single-nucleotide polymorphisms (SNPs) were genotyped in the Hong Kong cohort using TaqMan genotyping assay. Significant associations were validated in the Shantou and Beijing cohorts. RESULTS: Association of POAG with TLR4 rs7037117, in a recessive model, was identified in the Hong Kong and Shantou cohorts (both southern Chinese, p(rec)=0.0019) but not the Beijing cohort (northern Chinese). rs1533428 at chromosome 2p16.3 showed a consistent trend of age-specific association in all three cohorts. Genotypes TT + CT conferred a 2.16 fold of significantly increased risk to late-onset POAG (p(dom)=0.00025), but no significant risk to POAG of younger ages of onset in the combined cohort. A joint effect was found between rs7037117 and rs1533428, with carriers of both higher-risk genotypes having a 4.53 fold of increased disease risk (p=0.00028). CONCLUSIONS: Our study reveals discrepant association patterns of 12 candidate SNPs in 7 genes/loci with POAG in Chinese, provides positive replications for POAG markers rs1533428 at 2p16.3 and TLR4 rs7037117, and suggests that rs1533428 is a putative risk variant for late-onset POAG. The identification of an age-specific association between rs1533428 and late-onset POAG highlights a new genotype-phenotype association in POAG. Further studies are warranted to confirm the age-specific association.